Risk Analysis of Work Accidents in the Truck Maintenance Section of CV. Sumber Rejeki with FMEA and RCA Methods - Samudra, Akbar Ridhlo; Ismiyah, Elly; Hidayat, Hidayat (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
CV. Sumber Rejeki is one of the companies in the service sector that specializes in transporting goods using open trucks. The maintenance department is one of the parts of CV. Sumber Rejeki that has the task of ensuring the fleet operates properly, but during the truck repair process carried out, work accidents often occur. It is known that during the June-November 2023 period every month there must be an accident caused by the truck repair process. Therefore, in this study it is necessary to analyze the root of the problem in order to find out the right repair solution and the priority of repair actions. This research was conducted using FMEA and RCA methods. The FMEA results show that the priority of corrective actions lies in the pinched hand work accident. Then an analysis of the root of the problem with RCA was carried out so that an improvement solution was found in the form of using chain-block tools to lift heavier loads. In the future, it must carry out routine maintenance of work equipment and also control every work process to ensure the use of complete PPE by socializing the workmanship SOP. CV. Sumber Rejeki merupakan salah satu perusahaan di bidang jasa yang khusus melakukan pengangkutan barang dengan menggunakan truk terbuka. Departemen pemeliharaan merupakan salah satu bagian CV. Sumber Rejeki yang memiliki tugas memastikan armada beroperasi dengan baik, namun selama proses perbaikan truk yang dilakukan kerap kali terjadi kecelakaan kerja. Diketahui bahwa selama periode Juni–November 2023 tiap bulan pasti terjadi kecelakaan yang disebabkan pada proses perbaikan truk. Oleh karena itu, pada penelitian ini perlu dilakukan analisis akar masalah guna mengetahui tindak solusi perbaikan yang tepat beserta prioritas tindak perbaikan. Penelitian ini dilakukan dengan metode FMEA dan RCA. Hasil FMEA diketahui bahwa prioritas tindak perbaikan terletak pada kecelakaan kerja tangan terjepit. Kemudian dilakukan analisis akar masalah dengan RCA sehingga didapati solusi perbaikan berupa menggunakan alat bantu chain-block untuk mengangkat beban yang lebih berat. Dalam kedepannya harus melakukan perawatan peralatan kerja secara rutin dan juga mengontrol setiap proses pengerjaan untuk memastikan penggunakan APD lengkap dengan mensosialisasikan SOP pengerjaan.